The decision-making process in a rural community in Lesotho - Perry, J G, 1942- (Rhodes University, Faculty of Humanities, Department of Anthropology, 1978)
From Introduction: Lesotho is a small, mountainous country entirely surrounded by South Africa. The stark nature of its terrain and topography present harsh options to its inhabitants. Much of the country is mountainous, better suited to the keeping of stock than to agriculture. The lowlands, where the soils are more amenable to the plough, are scarred and cut by dongas. The soil is overworked and overcrowded and Lesotho does not grow enough to feed its people who depend on migrancy as a viable alternative to the limited resources of their own land. They stream from the country to seek wage employment in South Africa, for Lesotho has minimal industrial development and cannot provide jobs for her people. The civil service absorbs some of the educated elite, as does teaching, but the majority must sell their sweat in South Africa's service.
Keywords: Decision making -- Lesotho; Sotho (African people) -- Social life and customs; Local government -- Lesotho; Land tenure -- Lesotho; Thatched roofs -- Lesotho; Grasses -- Lesotho; Law -- Lesotho; Courts -- Lesotho; Community power -- Lesotho; Civic leaders -- Lesotho; Community life -- Lesotho; Lesotho -- Social conditions; Lesotho -- Rural conditions; Lesotho -- Politics and government